Analisa Kerusakan Pipa Bawah Laut Akibat dari Kejatuhan Jangkar - Aldara, Desta Rifky; DewI, Retno Syahriawati; Mulananda, Arisessy Maharani (Techno Bahari, 2022)
Subsea pipelines have several risks that can cause damage to the surrounding environment if damage occurs. Several factors can cause subsea pipeline failure, such as: third party errors, corrosion, design errors, and operational errors. Literature and historical reviews of subsea pipeline failures and incidents indicate that third party factors are responsible for 38% of subsea pipeline failures. Common factors from the category of third party errors that can cause pipeline failure include: fishing activities, commercial ship activities (emergency anchoring, dragged anchor, dropped containers, and ship sinking), and ship construction activities. The main focus of this assessment is the analysis of damage to the subsea pipeline caused by the anchor fall. Damage calculations based on the DNVGL RP F107 standard were compared with simulations using the FEM application. Based on the damage analysis carried out, the underwater pipeline was damaged in the protective concrete layer and experienced dents. Therefore, external protection using the gravel buried method is recommended to protect subsea pipelines from falling anchors. The total investment value required for the installation of the shield is Rp. 4,853,181,463.